KYRGYZ PHILOSOPHICAL THOUGHT AS AN OBJECT OF HISTORICAL AND PHILOSOPHICAL RESEARCH (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article discusses the problems and prospects of the research of philosophical thought of the Kyrgyz people. It is noted that in a short period of time, scientists of the republic have done significant work and accumulated a lot of theoretical material on the study of various aspects of the history of philosophical thought of the Kyrgyz people. However, the available research concerns only certain aspects of the problem, but not the philosophical thought of the Kyrgyz people as a whole. Also, problems have remained unexplored or poorly understood in the history of Kyrgyz philosophical thought.
Keywords: philosophy, society, thought, man, knowledge, faith, people, consciousness, research, object, aspect.